Democratisation and the Media. A Preliminary Discussion of Experiences in Europe and Asia - Sparks, Colin (Javnost-The Public, 2001)
Studies of the relationship of the mass media and democracy either rely very heavily on American and European experience, or they are focused studies of national cases. There are relatively few attempts to generalise from the rich diversity of the last thirty years. This article is an initial attempt to compare the experiences of the former communist countries of Central and Eastern Europe with the various dictatorships of East and South East Asia. It is argued that, despite the fact that there are important differences between communist and capitalist dictatorships, it is nevertheless theoretically possible to compare the two categories. An outline the-ory of the relationship between media and social power in both is introduced. In comparing Europe and Asia, it is argued that oppositions between .Western. and .Asian. values are not at all useful, despite their considerable popular currency at the time of writing (September 2001). In both cases, key democratic values like reason and media freedom have a contradictory status that defies continental generalisations. The article continues with an examination of the decay of the undemocratic regimes in the two continents and points to their differences and similarities. In particular, it is noted that there are surprising similarities of outcome in the media democratisation process despite the differences in starting point. The absence of radical democratic movements in Europe is contrasted with their apparently greater prominence in some parts of Asia. It is speculated that the future in China will involve political crises that will provide further opportunities for radical democratic movements.